Ni paste and multilayer ceramic capacitors

By adding specific additives to the Ni conductive film to form a diffusion region, the reliability problem of multi-layer ceramic capacitors at high temperatures and high electric fields is solved, and the high-temperature load life is improved and the conductive film continuity is maintained.

JP7655311B2Active Publication Date: 2025-04-02SHOEI CHEM IND CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2022515323
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-11
Filing Date
2021-04-06
Publication Date
2025-04-02
Estimated Expiration
2041-04-06

AI Technical Summary

Technical Problem

When manufacturing multi-layer ceramic capacitors, when Ni is used as the internal electrode material, the electric field strength increases after the dielectric layer is thinned, resulting in a decrease in the life of high-temperature load. The dissolution of Sn in Ni causes the continuity of the conductive film to decrease, affecting the reliability of the capacitor.

Method used

Additives such as Ta, Nb, stable zirconium (SZ) and Al are added to the Ni conductive film to control their mass fraction to form a diffusion area at the interface between the internal electrode and the dielectric layer, which slows down the movement of oxygen holes and thus improves the life of high-temperature load.

Benefits of technology

By using additives, the high-temperature load life of the multi-layer ceramic capacitor can be significantly improved without reducing the continuity of the internal electrode conductive film, and good reliability can be maintained under high electric field strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655311000009
    Figure 0007655311000009
  • Figure 0007655311000010
    Figure 0007655311000010
  • Figure 0007655311000011
    Figure 0007655311000011
Patent Text Reader

Abstract

An Ni paste which is characterized by containing (A) a conductive powder that is mainly composed of Ni, (B) a binder resin and (C) an organic solvent, and by additionally containing at least one substance that is selected from the group consisting of (D1) an additive that contains Ta in an amount within the range of from 0.025 to 2.50 parts by mass in terms of Ta2O5 per 100.0 parts by mass of the conductive powder (A) that is mainly composed of Ni, (D2) an additive that contains Nb in an amount within the range of from 0.010 to 1.80 parts by mass in terms of Nb2O5 per 100.0 parts by mass of the conductive powder (A) that is mainly composed of Ni, (D3) a stabilized zirconia (SZ) in an amount within the range of from 0.05 × 10-2 to 2.20 × 10-2 mol per 100 g of the conductive powder (A) that is mainly composed of Ni, said stabilized zirconia being obtained by stabilizing the crystal structure of zirconia by means of a stabilizer, and (D4) an additive that contains Al in an amount within the range of from 0.10 to 5.50 parts by mass in terms of A12O3 per 100.0 parts by mass of the conductive powder (A) that is mainly composed of Ni. The present invention is able to provide an Ni paste for internal electrodes, said Ni paste being capable of improving the high temperature load life without lowering the continuity of an electrode film.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a Ni paste for forming internal electrodes or the like for producing a highly reliable multilayer ceramic capacitor, and to a multilayer ceramic capacitor produced using the same. [Background technology]

[0002] With the recent development of electronics technology, there is an ever-increasing demand for smaller size and larger capacitance of multilayer ceramic capacitors. To meet these demands, progress is being made in thinning the dielectric layers that make up multilayer ceramic capacitors. However, when the dielectric layers are made thinner, the electric field strength applied to each layer becomes relatively higher. Therefore, there is a demand for improved reliability when voltage is applied.

[0003] Here, a multilayer ceramic capacitor is generally manufactured as follows. First, a dielectric ceramic raw material powder is dispersed in a resin binder, and a conductive paste for an internal electrode, mainly composed of a conductive powder and, if desired, an inorganic powder containing ceramic powder, etc., a resin binder, and a solvent, is printed in a predetermined pattern on a ceramic green sheet formed into a sheet, and the sheet is dried to remove the solvent, forming an internal electrode dry film. Next, a plurality of ceramic sheets having the obtained internal electrode dry film are stacked and pressed to form a laminate, which is cut into a predetermined shape and then fired at a high temperature to obtain a ceramic body. Thereafter, a conductive paste for an external electrode is applied to both end faces of the ceramic body, which is then fired to obtain a multilayer ceramic capacitor. Note that the external electrodes may be formed by applying a paste for an external electrode to an unfired laminate and firing the laminate simultaneously with the ceramic body. As an internal electrode, one using Ni as a main component is known (for example, Patent Document 1).

[0004] When manufacturing multilayer ceramic capacitors that use Ni as the main component in the internal electrodes, it is necessary to carry out sintering in a reducing atmosphere to prevent the Ni from oxidizing. However, this process introduces oxygen vacancies into the dielectric layer, which can cause a decrease in the high-temperature load life.

[0005] Therefore, Patent Document 2 describes an invention in which the height of the electrical barrier at the interface between the dielectric layer and the electrode layer is changed by using an internal electrode in which Sn is dissolved in Ni, thereby achieving a high-temperature loaded life. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent Publication No. 2001-101926 [Patent Document 2] WO2012 / 111592 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0007] However, when Sn dissolves in Ni, the melting point of Ni drops and sintering is accelerated, which makes it easier for ball-up to occur in various parts of the electrode layer during sintering, reducing the continuity of the electrode film, which in turn reduces the capacitance of the capacitor.

[0008] Therefore, an object of the present invention is to provide a Ni paste for internal electrodes that can improve the high temperature load life without reducing the continuity of the electrode film.Another object of the present invention is to provide a multilayer ceramic capacitor that exhibits excellent reliability even when the dielectric layer is further thinned and a voltage of high electric field strength is applied. [Means for solving the problem]

[0009] As a result of intensive research into solving the above problems, the inventors have discovered that by adding at least one selected from the group consisting of (D1) an additive containing Ta, (D2) an additive containing Nb, (D3) stabilized zirconia (SZ), and (D4) an additive containing Al to an Ni paste for internal electrodes containing (A) conductive powder mainly composed of Ni, in a predetermined ratio relative to the conductive powder mainly composed of Ni, it is possible to improve the high temperature load life without reducing the continuity of the electrode film, and have thus completed the present invention.

[0010] That is, the present invention (1) comprises: (A) a conductive powder mainly containing Ni; (B) a binder resin; (C) an organic solvent; Contains Furthermore, (D1) an additive containing Ta in an amount of 0.025 to 2.50 parts by mass, calculated as Ta2O5, per 100.0 parts by mass of the (A) Ni-based conductive powder; (D2) an additive containing Nb in a range of 0.010 to 1.80 parts by mass in terms of Nb2O5 per 100.0 parts by mass of the (A) Ni-based conductive powder; (D3) 0.05×10 per 100 g of the (A) Ni-based conductive powder -2 ~2.20×10 -2 Stabilized zirconia (SZ) in which the crystal structure of zirconia is stabilized by a stabilizer within the molar range, and (D4) an additive containing Al in an amount of 0.10 to 5.50 parts by mass in terms of Al2O3 per 100.0 parts by mass of the (A) Ni-based conductive powder; Contains at least one selected from the group consisting of: The present invention provides a Ni paste characterized by the above.

[0011] The present invention (2) also provides a Ni paste according to (1), characterized in that when the (D1) additive containing Ta is contained, the (D1) additive containing Ta is contained in an amount within a range of 0.025 to 0.80 parts by mass, calculated as Ta2O5, per 100.0 parts by mass of the (A) conductive powder mainly composed of Ni.

[0012] The present invention (3) also provides a Ni paste according to (1), characterized in that when the (D2) additive containing Nb is contained, the (D2) additive containing Nb is contained in an amount within a range of 0.010 to 0.50 parts by mass, calculated as Nb2O5, per 100.0 parts by mass of the (A) conductive powder mainly composed of Ni.

[0013] The present invention (4) also provides a Ni paste according to (1), characterized in that when the (D3) stabilized zirconia (SZ) is contained, the stabilizer is one or more selected from Y2O3, CaO, MgO and Sc2O3.

[0014] The present invention (5) also provides a Ni paste according to (4), characterized in that when the (D3) stabilized zirconia (SZ) is contained, the (D3) stabilized zirconia (SZ) contains the stabilizer in an amount of more than 0.0 mol % and not more than 45.0 mol %.

[0015] The present invention (6) provides a Ni paste according to (4), characterized in that, when the (D3) stabilized zirconia (SZ) is contained, the (D3) stabilized zirconia (SZ) contains the stabilizer in a range of 8.0 to 25.0 mol %.

[0016] In the present invention (7), when the (D3) stabilized zirconia (SZ) is contained, the (D3) stabilized zirconia (SZ) is added in an amount of 0.05×10 per 100 g of the (A) Ni-based conductive powder. -2 ~1.40×10 -2 The present invention provides a Ni paste according to any one of (1), (4) to (6), which is characterized by containing in the molar range of

[0017] The present invention (8) also provides a Ni paste according to (1), characterized in that when the (D4) additive containing Al is contained, the (D4) additive containing Al is contained in an amount within a range of 0.10 to 2.30 parts by mass, calculated as Al2O3, per 100.0 parts by mass of the (A) Ni-based conductive powder.

[0018] The present invention (9) also provides a Ni paste according to any one of (1) to (8), characterized in that the content of the conductive powder mainly composed of Ni (A) is 30.0 to 95.0 mass %.

[0019] The present invention (10) also provides a ceramic laminate in which a plurality of ceramic dielectric layers and a plurality of internal electrode layers containing Ni are alternately laminated, an external electrode formed on an outer surface of the ceramic laminate; Equipped with The ceramic laminate is (D1) Ta in a range of 0.025 to 2.50 parts by mass in terms of Ta2O5 per 100.0 parts by mass of the (A) Ni-containing conductive component, (D2) Nb in a range of 0.010 to 1.80 parts by mass in terms of Nb2O5 per 100.0 parts by mass of the (A) Ni-containing conductive component, and (D4) (A) Al in the range of 0.10 to 5.50 parts by mass in terms of Al2O3 per 100.0 parts by mass of the Ni-containing conductive component Contains at least one selected from the group consisting of: The present invention provides a multilayer ceramic capacitor characterized by the above.

[0020] The present invention (11) also relates to a ceramic laminate in which a plurality of ceramic dielectric layers and a plurality of internal electrode layers containing Ni are alternately laminated, an external electrode formed on an outer surface of the ceramic laminate; Equipped with A diffusion region of at least one element selected from the group consisting of Ta, Nb, Zr, a metal element in a stabilizer, and Al is provided at and near the interface between the adjacent internal electrode layer and the ceramic dielectric layer. The present invention provides a multilayer ceramic capacitor characterized by the above.

[0021] The present invention (12) also provides a multilayer ceramic capacitor according to (11), characterized in that the metal element in the stabilizer is at least one selected from the group consisting of Y, Ca, Mg and Sc.

[0022] The present invention (13) also provides a ceramic laminate in which a plurality of ceramic dielectric layers and a plurality of internal electrode layers containing Ni are alternately laminated, an external electrode formed on an outer surface of the ceramic laminate; Equipped with The internal electrode layers are formed of a sintered product obtained by sintering any one of the Ni pastes (1) to (9) at 900 to 1400 ° C.; The present invention provides a multilayer ceramic capacitor characterized by the above. Effect of the Invention

[0023] According to the present invention, it is possible to provide a Ni paste for internal electrodes that can improve the high temperature load life without reducing the continuity of the electrode film. Also, according to the present invention, it is possible to provide a multilayer ceramic capacitor that exhibits excellent reliability even when the dielectric layer is further thinned and a voltage of high electric field strength is applied. [Brief description of the drawings]

[0024] [Figure 1] 1 is a graph showing the relationship between Ta2O5 and MTTF (Ta2O5 added) / MTTF (no addition) in Table 1 of Example 1. [Diagram 2] 1 is a graph showing the relationship between Nb2O5 and MTTF (Nb2O5 added) / MTTF (no addition) in Table 2 of Example 1. [Diagram 3]1 is a graph showing the relationship between MTTF (ZrO2 added) / MTTF (no addition) in Comparative Example 1 and MTTF (YSZ added) / MTTF (no addition) in Example 2. [Figure 4] 1 is a graph showing the relationship between the MTTF of Example 2 (YSZ added) and the MTTF of Comparative Example 1 (ZrO 2 added). [Diagram 5] 13 is a graph showing the relationship between MTTF (YSZ added) / MTTF (no addition) in Example 3 and MTTF (YSZ added) / MTTF (ZrO 2 added) in Example 3. [Figure 6] 1 is a graph showing the relationship between Al2O3 and MTTF (Al2O3 added) / MTTF (no addition) in Table 8 of Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The Ni paste of the present invention is (A) a conductive powder mainly containing Ni; (B) a binder resin; (C) an organic solvent; Contains Furthermore, (D1) an additive containing Ta in an amount of 0.025 to 2.50 parts by mass, calculated as Ta2O5, per 100.0 parts by mass of the (A) Ni-based conductive powder; (D2) an additive containing Nb in a range of 0.010 to 1.80 parts by mass in terms of Nb2O5 per 100.0 parts by mass of the (A) Ni-based conductive powder; (D3) 0.05×10 per 100 g of the (A) Ni-based conductive powder -2 ~2.20×10 -2 Stabilized zirconia (SZ) in which the crystal structure of zirconia is stabilized by a stabilizer within the molar range, and (D4) an additive containing Al in an amount of 0.10 to 5.50 parts by mass in terms of Al2O3 per 100.0 parts by mass of the (A) Ni-based conductive powder; Contains at least one selected from the group consisting of: This is a Ni paste characterized by the above.

[0026] An example of the Ni paste of the present invention is a Ni paste characterized by containing (A) a conductive powder mainly composed of Ni, (B) a binder resin, and (C) an organic solvent, and further containing (D1) an additive containing Ta in a range of 0.025 to 2.50 parts by mass, calculated as Ta2O5, per 100.0 parts by mass of the (A) conductive powder mainly composed of Ni. Moreover, the Ni paste of the present invention includes a Ni paste characterized by containing (A) a conductive powder mainly composed of Ni, (B) a binder resin, and (C) an organic solvent, and further containing (D2) an additive containing Nb in a range of 0.010 to 1.80 parts by mass, calculated as Nb2O5, per 100.0 parts by mass of the (A) conductive powder mainly composed of Ni. The Ni paste of the present invention contains (A) a conductive powder mainly composed of Ni, (B) a binder resin, and (C) an organic solvent, and further contains (D3) 0.05×10 -2 ~2.20×10 -2 The Ni paste is characterized by containing stabilized zirconia (SZ) in which the crystal structure of zirconia is stabilized by a stabilizer within a molar range. Moreover, the Ni paste of the present invention includes a Ni paste characterized by containing (A) a conductive powder mainly composed of Ni, (B) a binder resin, and (C) an organic solvent, and further containing (D4) an additive containing Al in an amount of 0.10 to 5.50 parts by mass, calculated as Al2O3, per 100.0 parts by mass of the (A) conductive powder mainly composed of Ni.

[0027] The Ni paste of the present invention is suitably used for forming internal electrodes of multilayer ceramic capacitors, and can also be applied to other ceramic electronic components such as multilayer ceramic actuators.

[0028] The Ni paste of the present invention contains at least (A) a conductive powder mainly composed of Ni, (B) a binder resin, (C) an organic solvent, and "at least one selected from the group consisting of (D1) an additive containing Ta, (D2) an additive containing Nb, (D3) stabilized zirconia (SZ), and (D4) an additive containing Al." In other words, the Ni paste of the present invention contains at least (A) a conductive powder mainly composed of Ni, (B) a binder resin, (C) an organic solvent, and one or more of (D1) an additive containing Ta, (D2) an additive containing Nb, (D3) stabilized zirconia (SZ), and (D4) an additive containing Al.

[0029] The Ni-based conductive powder (A) according to the Ni paste of the present invention is used as a conductive powder in the Ni paste for forming an internal electrode, and is a powder mainly containing Ni. The Ni-based conductive powder (A) may be a powder consisting of metal Ni alone. The Ni-based conductive powder (A) may be a composite powder of Ni and other compounds, a mixed powder of Ni and other compounds, an alloy powder of Ni and other metals, etc., as long as it provides the effects of the present invention. The Ni-based composite powder may be, for example, a composite powder in which the surface of Ni powder is covered with a glassy thin film, a composite powder in which the surface of Ni powder is covered with an oxide, or a composite powder in which the surface of Ni powder is surface-treated with an organometallic compound, a surfactant, a fatty acid, or the like. The Ni-based mixed powder may be, for example, a mixed powder of Ni powder and an oxide powder. Other metals that can be used in the alloy powder are metals that are unlikely to cause a melting point drop when alloyed with Ni, or even if they do cause a melting point drop, they may be contained in an amount that does not cause the previously mentioned ball-up phenomenon, and examples include Cu, Ag, Pd, Pt, Rh, Ir, Re, Ru, Os, In, Ga, Zn, Bi, Pb, Fe, V, and Y. (A) The Ni content in the Ni-based conductive powder is not particularly limited as long as it provides the effects of the present invention, but is preferably 60.0 mass% or more, particularly preferably 80.0 mass% or more, and even more preferably 100.0 mass%.

[0030] The average particle size of the conductive powder mainly containing Ni (A) is not particularly limited, but is preferably 0.05 to 1.0 μm. When the average particle size of the conductive powder mainly containing Ni (A) is within the above range, a dense, smooth and thin internal electrode layer is easily formed. In this specification, the symbol "~" indicating a numerical range indicates a range including the numerical values ​​written before and after the symbol "~", unless otherwise specified. That is, for example, the expression "0.05 to 1.0" is synonymous with "0.05 or more and 1.0 or less" unless otherwise specified.

[0031] In the Ni paste of the present invention, the content of the conductive powder mainly composed of (A) Ni is not particularly limited, and may be appropriately selected usually within the range of 30.0 to 95.0 mass %, taking into consideration the finished viscosity, printability, storage stability, etc. of the Ni paste.

[0032] The (B) binder resin in the Ni paste of the present invention is not particularly limited as long as it can be used in a conductive paste for forming an internal electrode. (B) Binder resins include those generally used in conductive pastes for forming internal electrodes, such as cellulose-based resins such as ethyl cellulose, acrylic resins, methacrylic resins, butyral resins, epoxy resins, phenolic resins, and rosin.

[0033] The content ratio of the (B) binder resin in the Ni paste of the present invention is not particularly limited, and is usually 0.1 to 30.0 parts by mass, and preferably 1.0 to 15.0 parts by mass, per 100.0 parts by mass of the (A) Ni-based conductive powder.

[0034] The (C) organic solvent for the Ni paste of the present invention is not particularly limited as long as it dissolves the (B) binder resin, and examples thereof include alcohol-based, ether-based, ester-based, and hydrocarbon-based solvents, as well as mixed solvents thereof.

[0035] The Ni paste of the present invention contains (A) a conductive powder mainly composed of Ni, (B) a binder resin, and (C) an organic solvent, as well as at least one selected from the group consisting of (D1) an additive containing Ta, (D2) an additive containing Nb, (D3) stabilized zirconia (SZ), and (D4) an additive containing Al.

[0036] The component (D1) in the Ni paste of the present invention is an additive containing Ta. The additive containing Ta is not particularly limited as long as it can obtain Ta2O5 after firing the Ni paste, but examples include pure metal (Ta), inorganic compounds such as oxides (Ta2O5, TaO2), sulfides (TaS2), halides (TaF5, etc.), and borides (TaB) containing Ta, and organometallic compounds such as metal carbonyls, metal alkoxides, and metal resinates. In the present invention, Ta2O5 is particularly preferred as the additive containing Ta.

[0037] When the Ni paste of the present invention contains (D1) an additive containing Ta, the Ni paste of the present invention contains the Ta-containing additive in a proportion of 0.025 to 2.50 parts by mass, preferably 0.025 to 0.80 parts by mass, per 100.0 parts by mass of the (A) Ni-based conductive powder, when converted to Ta2O5.

[0038] The component (D2) in the Ni paste of the present invention is an additive containing Nb. The additive containing Nb is not particularly limited as long as it can obtain Nb2O5 after firing the Ni paste, but examples include pure metal (Nb), inorganic compounds such as oxides (Nb2O5, NbO2), sulfides (NbS2), halides (NbF5, etc.), and borides (NbB) containing Nb, and organic metal compounds such as metal carbonyls, metal alkoxides, and metal resinates. In the present invention, Nb2O5 is particularly preferred as the additive containing Nb.

[0039] When the Ni paste of the present invention contains (D2) an additive containing Nb, the Ni paste of the present invention contains the additive containing Nb in a proportion of 0.010 to 1.80 parts by mass, preferably 0.010 to 0.50 parts by mass, per 100.0 parts by mass of the conductive powder mainly composed of Ni (A), when Nb2O5 is converted into Nb2O5.

[0040] The component (D3) in the Ni paste of the present invention is stabilized zirconia (SZ) in which the crystal structure of zirconia is stabilized by a stabilizer. Stabilized zirconia (SZ) is made by dissolving a stabilizer in zirconia (ZrO2) and inserting a divalent or trivalent metal element into the tetravalent Zr site, thereby stabilizing the crystal structure of zirconia (ZrO2) so that it does not change due to temperature changes.

[0041] The stabilizer is not particularly limited as long as it stabilizes zirconia (ZrO2), and examples of the stabilizer include oxides of alkaline earth metals such as MgO, CaO, SrO, BaO, etc.; oxides of rare earth elements such as Sc2O3, Y2O3, La2O3, CeO2, Pr2O3, Nd2O3, Sm2O3, Eu2O3, Gd2O3, Tb2O3, Dy2O3, Er2O3, Tm2O3, Yb2O3, etc.; and one or more oxides selected from Bi2O3, In2O3, etc.

[0042] Among them, in the present invention, it is preferable that the zirconia is stabilized with one or more selected from yttria (Y2O3), calcia (CaO), magnesia (MgO) and scandia (Sc2O3). The stabilizer used in the stabilized zirconia (SZ) may be one type or a combination of two or more types.

[0043] In this specification, when the stabilized zirconia in general is intended without specifying the stabilizer, the stabilized zirconia may be written as "SZ". When the stabilized zirconia using yttria (Y2O3), calcia (CaO), magnesia (MgO) and scandia (Sc2O3) as stabilizers is intended, the stabilized zirconia may be written as "YSZ", "CSZ", "MSZ" and "ScSZ", respectively. Furthermore, the stabilized zirconia (SZ) containing X (mol%) of stabilizer may be written as "X-SZ". For example, "3.0-YSZ" means stabilized zirconia (YSZ) stabilized with 3.0 mol% yttria (Y2O3).

[0044] The content of the stabilizer in the stabilized zirconia (SZ) is not particularly limited, but is preferably more than 0.0 mol% and not more than 45.0 mol%, more preferably more than 0.0 mol% and not more than 40.0 mol%, and particularly preferably 8.0 to 25.0 mol%. By having the content of the stabilizer in the stabilized zirconia (SZ) within the above range, it becomes easier to improve the high temperature load life. The content of the stabilizer in the stabilized zirconia (SZ) (X mol%) is calculated by converting Zr in the stabilized zirconia (SZ) and the metal elements in the stabilizer into oxides, respectively, and calculating the percentage of the number of moles of the metal elements in the stabilizer in terms of oxides relative to the total number of moles of Zr and the metal elements in the stabilizer in terms of oxides ((the number of moles of the metal elements in the stabilizer in terms of oxides / (the number of moles of the metal elements in the stabilizer in terms of oxides+the number of moles of Zr in the stabilized zirconia (SZ) in terms of oxides))×100). For oxide conversion, for example, Zr is converted to ZrO2, Y to Y2O3, Ca to CaO, Mg to MgO, and Sc to Sc2O3, and the number of moles is calculated. When stabilized zirconia (SZ) contains two or more stabilizers, each metal element in the two or more stabilizers is converted to its oxide, and the total number of moles of these oxides is the number of moles of the metal elements in the stabilizer in oxide conversion.

[0045] When the Ni paste of the present invention contains (D3) stabilized zirconia (SZ), the content of (D3) stabilized zirconia (SZ) in the Ni paste of the present invention is 0.05 × 10 per 100.0 g of (A) Ni-based conductive powder. -2 ~2.20×10 -2 Molar, preferably 0.05 x 10 -2 ~1.40×10 -2 The content of stabilized zirconia (SZ) in the Ni paste is in moles. By having the content of stabilized zirconia (SZ) in the above range, the high temperature load life can be improved. The content of stabilized zirconia (SZ) in the Ni paste is calculated by converting Zr in the stabilized zirconia (SZ) and the metal elements in the stabilizer into oxides, respectively, determining the total moles of Zr and the metal elements in the stabilizer converted into oxides, and calculating the number of moles per 100.0 g of the conductive powder mainly composed of (A) Ni.

[0046] The component (D4) in the Ni paste of the present invention is an additive containing Al. The additive containing Al is not particularly limited as long as it can obtain Al2O3 after firing the Ni paste, but examples include pure metal (Al), inorganic compounds such as oxides (Al2O3), sulfides (Al2S3), halides (AlF3, etc.), borides (AlB2), nitrides (AlN), carbides (Al4C3), hydroxides (Al(OH)3), phosphates (AlPO4), and sulfates (Al2(SO4)3) containing Al, and organic metal compounds such as metal alkoxides and metal resinates. In the present invention, Al2O3 is particularly preferred as the additive containing Al.

[0047] When the Ni paste of the present invention contains (D4) an additive containing Al, the Ni paste of the present invention contains the additive containing Al in a proportion of 0.10 to 5.50 parts by mass, preferably 0.10 to 2.30 parts by mass, per 100.0 parts by mass of the conductive powder mainly composed of (A) Ni, when the Al in the additive containing Al is converted to Al2O3.

[0048] The Ni paste of the present invention may contain a combination of (D1) a Ta-containing additive, (D2) an Nb-containing additive, (D3) stabilized zirconia (SZ), and (D4) an Al-containing additive.

[0049] The mechanism by which the Ni paste of the present invention obtains the above-mentioned effects by containing at least one selected from the group consisting of (D1) an additive containing Ta, (D2) an additive containing Nb, (D3) stabilized zirconia (SZ), and (D4) an additive containing Al in the above-mentioned content ratio is not clear. However, according to the tests and researches by the present inventors, most of the Ta component, Nb component, stabilized zirconia (SZ) component, or Al component contained in the Ni paste migrates to the ceramic dielectric layer side during firing of the paste, and as a result, it was observed that a diffusion region (diffusion layer) containing Ta, Nb, Zr, and metal elements in the stabilizer, or Al in high concentration was formed at the interface between the ceramic dielectric layer and the internal electrode layer and its vicinity after firing. In addition, in the present invention, "the interface and its vicinity" refers to the region from the interface between the ceramic dielectric layer and the internal electrode layer to the dielectric layer side up to 1 / 16 of the ceramic dielectric layer thickness to the internal electrode layer side up to 1 / 2 of the internal electrode layer thickness from the interface. The inventors speculate that the presence of this diffusion region (diffusion layer) reduces the rate at which oxygen vacancies in the ceramic dielectric layer move toward the cathode during high-temperature load life tests, thereby improving the life span. In addition, even if a co-material powder containing Zr is used in the Ni paste using (D3) stabilized zirconia (SZ), the composition of the co-material powder is the same as or similar to that of the ceramic dielectric layer, so even if it diffuses from the internal electrode layer to the ceramic dielectric layer during firing, there is almost no change in the element concentration distribution of Zr in the ceramic dielectric layer. Therefore, the formation of a diffusion region (diffusion layer) containing high concentrations of Zr and metal elements in the stabilizer observed at and near the interface between the ceramic dielectric layer and the internal electrode layer is thought to be due to the stabilized zirconia (SZ) contained in the Ni paste separately from the co-material powder. Moreover, stabilized zirconia (SZ) is zirconia (ZrO2) with oxygen vacancies introduced, and the more stabilizer, the more oxygen vacancies there are, so by adding stabilized zirconia (SZ) to the Ni paste, the oxygen vacancy concentration near the interface can be increased more than when non-stabilized zirconia (ZrO2) is added. As a result, in a high-temperature load life test, oxygen vacancies inside the dielectric layer are less likely to move to the electrode interface (cathode), further improving the high-temperature load life. On the other hand, if the amount of stabilizer is excessive, the oxygen vacancy concentration becomes too high, which is thought to cause a rapid decline in the high-temperature load life characteristics. In addition, the inclusion of Ta, Nb, stabilized zirconia (SZ) or Al in the internal electrode layer after firing does not lower the melting point of Ni, and therefore does not adversely affect the continuity of the electrode film. However, if the concentration of Ta, Nb, stabilized zirconia (SZ) or Al in the diffusion layer in the ceramic dielectric layer becomes too high, the wettability with Ni decreases, which may adversely affect the continuity of the electrode film. If the content of (D1) the Ta-containing additive, (D2) the Nb-containing additive, (D3) the stabilized zirconia (SZ) content, or (D4) the Al-containing additive in the Ni paste is less than the above range, the effect of improving the high-temperature loaded life cannot be obtained. On the other hand, if it exceeds the above range, crystal grain growth occurs due to the Ta component, Nb component, stabilized zirconia (SZ) component, or Al component diffused into the ceramic dielectric layer, resulting in a decrease in the high-temperature loaded life.

[0050] The Ni paste of the present invention may further contain a co-material powder that is usually added to Ni paste for forming internal electrodes. The co-material powder is intended to approximate the sintering shrinkage behavior of the internal electrodes to that of the dielectric layer, and the type of the co-material powder is not particularly limited, but is desirably selected so that the change in the characteristics of the capacitor due to the reaction with the ceramic dielectric is minimized. As the co-material powder, ceramic powders represented by the general formula: ABO3 (wherein A is at least one of Ba, Ca, and Sr, and B is at least one of Ti, Zr, and Hf) that are usually used in Ni paste for forming internal electrodes, such as perovskite-type oxide powders such as barium titanate, strontium zirconate, and calcium zirconate, or powders to which various additives have been added, are preferred. In addition, the co-material powder is preferably one having the same composition as or similar to the dielectric ceramic raw material powder used as the main component of the dielectric layer. The co-material powder may be attached in advance to the surface of the conductive powder mainly composed of (A) Ni, and then mixed with other components in the Ni paste.

[0051] When the Ni paste of the present invention contains a common material powder, the content ratio of the common material powder in the Ni paste of the present invention is a ratio in which the total of the common material powder is 30.0 parts by mass or less per 100.0 parts by mass of the conductive powder mainly composed of (A) Ni. If the content ratio of the common material powder in the Ni paste exceeds the above range, the electrode layer becomes thick, which makes it easier for structural defects to occur, and the electrode layer becomes a discontinuous film.

[0052] The average particle size of the common material powder is not particularly limited, but it is preferable that it is 30% or less of the average particle size of the conductive powder mainly made of (A) Ni, since it shows a better sintering suppression effect and a better denseness improvement effect. Furthermore, it is preferable that the total specific surface area of ​​the common material powder in the paste is larger than the total specific surface area of ​​the conductive powder mainly made of (A) Ni, since it enhances the effect of improving the high temperature load life. Note that, by selecting the average particle size and content of the common material powder, the total specific surface area of ​​the common material powder in the paste can be made larger than the total specific surface area of ​​the conductive powder mainly made of (A) Ni. However, if the average particle size of the common material powder is too small, the sintering of the powder itself becomes too fast due to the increase in surface area, and the sintering suppression effect of the conductive powder mainly made of Ni is reduced, so the average particle size of the common material powder is preferably 0.01 μm or more.

[0053] The Ni paste of the present invention may contain known compounds containing metal elements other than those mentioned above, as long as they do not impair the effects of the present invention. For example, compounds such as CaO, ZrO2, Y2O3, Ti4O7, TiO2, Co3O4, Fe2O3, La2O3, Li2O, MgO, MoO3, SrO, V2O5, WO3, and CuO may be added for various purposes. In addition, the present invention does not exclude the inclusion of an Sn component. It is believed that Sn alloys with Ni during firing to lower the melting point and promote sintering, which causes the above-mentioned ball-up phenomenon. Therefore, a Sn compound that does not alloy with Ni should be used, or it may be used in combination with (D1) an additive containing Ta, (D2) an additive containing Nb, (D3) stabilized zirconia (SZ), or (D4) an additive containing Al, as long as the content is such that the ball-up phenomenon does not occur even if the Sn compound is alloyed.

[0054] In addition to the above, the Ni paste of the present invention may contain additives such as plasticizers, dispersants, and surfactants that are usually added to Ni pastes for forming internal electrodes, as necessary.

[0055] The Ni paste of the present invention is prepared by uniformly mixing and dispersing the above-mentioned (A) conductive powder mainly composed of Ni, (B) binder resin, (C) organic solvent, "at least one selected from the group consisting of (D1) an additive containing Ta, (D2) an additive containing Nb, (D3) stabilized zirconia (SZ), and (D4) an additive containing Al," as well as other co-material powders and various additives added as necessary, according to a conventional method.

[0056] The multilayer ceramic capacitor of the present invention is produced by the following method using the Ni paste of the present invention.

[0057] First, the dielectric ceramic raw material powder is dispersed in a resin binder, and the powder is formed into a sheet by a doctor blade method, a die coater method, or the like, to prepare a ceramic green sheet containing the dielectric ceramic raw material powder. As the dielectric ceramic raw material powder for forming the dielectric layer, a powder mainly composed of a perovskite type oxide such as a barium titanate type, a strontium zirconate type, or a calcium strontium zirconate type perovskite type oxide, or a powder in which a part of the metal elements constituting these oxides is replaced with other metal elements, is used. If necessary, various additives for adjusting the capacitor characteristics are mixed into these raw material powders. For example, when the thickness of the dielectric ceramic layer is set to 5.0 μm or less, the average particle size of the raw material powder is preferably about 0.05 to 0.4 μm. Next, the Ni paste of the present invention is applied on the obtained ceramic green sheet by a normal method such as screen printing, and the Ni paste is dried to remove the solvent, to form an internal electrode paste dry film of a predetermined pattern. Next, a predetermined number of ceramic green sheets on which the internal electrode paste film is formed are stacked and heated and pressed to prepare an unfired laminate. The resulting laminate is then cut into a desired shape and fired at a high temperature to simultaneously sinter the dielectric layers and electrode layers to obtain a laminated ceramic capacitor body. Terminal electrodes are then fired onto both end faces of the body to obtain the laminated ceramic capacitor of the present invention. The terminal electrodes may be attached before firing the laminate and fired simultaneously with the laminate.

[0058] The multilayer ceramic capacitor of the present invention thus obtained comprises a ceramic laminate in which a plurality of ceramic dielectric layers and a plurality of Ni-containing internal electrode layers are alternately laminated, an external electrode formed on an outer surface of the ceramic laminate; Equipped with The ceramic laminate is (D1) Ta in a range of 0.025 to 2.50 parts by mass in terms of Ta2O5 per 100.0 parts by mass of the (A) Ni-containing conductive component, (D2) Nb in a range of 0.010 to 1.80 parts by mass in terms of Nb2O5 per 100.0 parts by mass of the (A) Ni-containing conductive component, and (D4) (A) Al in the range of 0.10 to 5.50 parts by mass in terms of Al2O3 per 100.0 parts by mass of the Ni-containing conductive component Contains at least one selected from the group consisting of: The laminated ceramic capacitor is characterized by the above.

[0059] The multilayer ceramic capacitor of the present invention includes a ceramic laminate in which a plurality of ceramic dielectric layers and a plurality of internal electrode layers containing Ni are alternately laminated; an external electrode formed on an outer surface of the ceramic laminate; Equipped with A diffusion region (diffusion layer) having a concentration peak of at least one element selected from the group consisting of Ta, Nb, Zr, metal elements in a stabilizer, and Al is provided at the interface between the adjacent internal electrode layer and the ceramic dielectric layer and in the vicinity thereof, i.e., in any part within a range from a region from the interface between the ceramic dielectric layer and the internal electrode layer to a region on the dielectric layer side that is 1 / 16 of the ceramic dielectric layer thickness to a region from the interface to a region on the internal electrode layer side that is 1 / 2 of the internal electrode layer thickness, The laminated ceramic capacitor is characterized by the above. The diffusion region is a region having a concentration distribution in which the concentration of at least one element selected from the group consisting of Ta, Nb, Zr, metal elements in the stabilizer, and Al increases in a direction from the internal electrode layer side to the ceramic dielectric layer side, reaches a concentration peak, and then decreases. The metal element in the stabilizer is preferably at least one selected from the group consisting of Y, Ca, Mg and Sc.

[0060] The ceramic dielectric layers of the multilayer ceramic capacitor of the present invention are formed by using, as a dielectric ceramic raw material powder, a powder mainly composed of a typical perovskite oxide, such as a perovskite oxide based on barium titanate, strontium zirconate, calcium strontium zirconate, or the like, or an oxide in which some of the metal elements constituting these are replaced with other metal elements, forming the dielectric ceramic raw material powder into a sheet, and firing the sheet at 900 to 1400°C, preferably 1100 to 1300°C, in a reducing atmosphere.

[0061] The multilayer ceramic capacitor of the present invention is formed by forming the Ni-containing internal electrode layer using the Ni paste of the present invention, that is, forming the Ni paste of the present invention on a ceramic green sheet for forming a dielectric layer by screen printing or the like, drying, and firing. As described above, most of the Ta component, Nb component, stable zirconia (SZ) component, or Al component contained in the Ni paste migrates from the internal electrode layer to the ceramic dielectric layer side during firing, and forms a diffusion region (diffusion layer) containing Ta, Nb, Zr, and metal elements in the stabilizer, or Al at a high concentration at the interface between the internal electrode layer and the ceramic dielectric layer and in the vicinity thereof. Note that the concentration distribution of Ta, Nb, Zr, and metal elements in the stabilizer, or Al in the diffusion region (diffusion layer) is not uniform, and the concentration of Ta, Nb, Zr, and metal elements in the stabilizer, or Al increases in the direction from the internal electrode layer side to the dielectric layer side, reaches a concentration peak, and then decreases. From the research results up to this stage, it is assumed that the concentration peak is near the interface, but its position has not yet been accurately identified. That is, the thickness of the diffusion layer, the shape of the concentration gradient, and the position of the concentration peak differ depending on the firing profile, such as the firing temperature, firing time, and temperature rise rate. For example, in an experimental example using an additive containing Ta, when the temperature was raised rapidly and firing was performed for a short time, the Ta component diffused from the internal electrode layer toward the dielectric layer, and a diffusion layer with a steep concentration gradient (concentration peak) in which Ta was unevenly distributed only at a position very close to the interface with the internal electrode layer was formed in the dielectric layer. In another experimental example, when firing was performed for a long time, Ta was hardly observed in the internal electrode layer, and a diffusion layer with a relatively broad Ta concentration gradient (concentration peak) was formed in the dielectric layer.

[0062] Therefore, the multilayer ceramic capacitor of the present invention is characterized by containing at least one selected from the group consisting of (D1) Ta in a range of 0.025 to 2.50 parts by mass, preferably 0.025 to 0.80 parts by mass, calculated as Ta2O5, per 100.0 parts by mass of the conductive component containing Ni (A), (D2) Nb in a range of 0.010 to 1.80 parts by mass, preferably 0.010 to 0.50 parts by mass, calculated as Nb2O5, per 100.0 parts by mass of the conductive component containing Ni (A), and (D4) Al in a range of 0.10 to 5.50 parts by mass, preferably 0.10 to 2.30 parts by mass, calculated as Al2O3, per 100.0 parts by mass of the conductive component containing Ni (A). The multilayer ceramic capacitor of the present invention includes a ceramic laminate in which a plurality of ceramic dielectric layers and a plurality of internal electrode layers containing Ni are alternately laminated; an external electrode formed on an outer surface of the ceramic laminate; Equipped with The ceramic dielectric layer is characterized by having a diffusion region (diffusion layer) of at least one element selected from the group consisting of Ta, Nb, Zr, a metal element in a stabilizer, and Al at and near the interface between the adjacent internal electrode layer and the ceramic dielectric layer. The metal element in the stabilizer is preferably at least one element selected from the group consisting of Y, Ca, Mg, and Sc. Furthermore, due to the above-mentioned characteristics, the multilayer ceramic capacitor of the present invention has an improved high-temperature accelerated life, and therefore exhibits excellent reliability even when the dielectric layers are made thinner and a voltage of high electric field strength is applied.

[0063] Furthermore, the fact that the dielectric layer and internal electrode layer contain Ta, Nb, stabilized zirconia (SZ) or Al components, and that they have a diffusion region (diffusion layer) with a concentration distribution in which the contents increase in the direction from the internal electrode layer side to the ceramic dielectric layer side, reach a concentration peak and then decrease, can be confirmed by combining an SEM (scanning electron microscope), a TEM (transmission electron microscope), or a STEM (scanning transmission electron microscope) with an elemental analysis method such as EDS (energy dispersive X-ray spectroscopy), WDS (wavelength dispersive X-ray spectroscopy), or EELS (electron energy loss spectroscopy).

[0064] The Ni-containing internal electrode layers of the multilayer ceramic capacitor of the present invention are formed by firing the Ni paste of the present invention at 900 to 1400° C., preferably 1100 to 1300° C. in a reducing atmosphere.

[0065] There are no particular limitations on the external electrodes of the multilayer ceramic capacitor of the present invention, so long as they can be used as external electrodes of a multilayer ceramic capacitor.

[0066] The multilayer ceramic capacitor of the present invention includes a ceramic laminate in which a plurality of ceramic dielectric layers and a plurality of internal electrode layers containing Ni are alternately laminated; an external electrode formed on an outer surface of the ceramic laminate; Equipped with The internal electrode layers are formed of a sintered product obtained by sintering the Ni paste of the present invention at 900 to 1400 ° C.; The laminated ceramic capacitor is characterized by the above.

[0067] In the multilayer ceramic capacitor of the present invention, the internal electrode layer is formed by screen printing or the like of the Ni paste of the present invention on a ceramic green sheet for forming a laminated layer, drying, and firing. The firing temperature of the Ni paste of the present invention is 900 to 1400 ° C, preferably 1100 to 1300 ° C, and the firing atmosphere is a reducing atmosphere. That is, the internal electrode layer is formed of a fired product of the Ni paste of the present invention at 900 to 1400 ° C, preferably 1100 to 1300 ° C.

[0068] Hereinafter, the present invention will be described based on specific experimental examples, but the present invention is not limited thereto.

Example

[0069] <<(D1) Additive containing Ta and (D2) Additive containing Nb>> (Example 1) <Manufacture of Ni paste and multilayer ceramic capacitor> To 100.0 g of spherical nickel powder having an average particle diameter of 0.3 μm, Ta2O5 or Nb2O5 was added at a ratio of parts by mass shown in Table 1 or Table 2. As a co-material powder, 10.0 g of BaTiO3 powder having an average particle diameter of 0.05 μm, 6.0 g of ethyl cellulose (binder resin), 2.0 g of surfactant, 1.0 g of plasticizer, and 100.0 g of dihydroterpineol acetate (organic solvent) were mixed and kneaded using a three-roll mill to prepare a Ni paste. Next, a polyvinyl butyral-based binder, ethanol, and an additive for adjusting capacitor characteristics were added to BaTiO3 powder having an average particle diameter of 0.2 μm, which is the main component of the ceramic green sheet, and wet-mixed by a media mill to prepare a ceramic slurry. This ceramic slurry was formed into a sheet by the die coater method to prepare a ceramic green sheet having a thickness of 5.5 μm. Next, Ni paste was printed on the ceramic green sheet in a rectangular pattern of 1.5 mm x 3.0 mm, and then dried to form an internal electrode dry film. The thickness of the internal electrode dry film was 1.5 μm. The ceramic green sheets with the internal electrode dry film were stacked so that the number of dielectric effective layers was 50, and the sheets were subjected to a pressure of 1250 kg / cm at 90°C. 2 The mixture was pressed and molded under a pressure of 1000 MPa to obtain an unfired ceramic laminate. This ceramic laminate was heated to 700°C in an atmosphere of N2-0.1%H2-H2O gas to burn the binder, and then the oxygen partial pressure at 1220°C was 1×10 -8 The material was heated at a rate of 5°C / min in a reducing atmosphere of N2-0.1% H2-H2O gas at 1 atm, and then held at 1220°C for 2 hours to sinter and densify it. After that, in the cooling stage, a reoxidation treatment was performed at 1000°C for 3 hours in an N2-H2O gas atmosphere to obtain a laminated ceramic body. Next, a Cu paste for forming external electrodes containing Cu powder and BaO-based glass frit was applied to both end faces of the multilayer ceramic body, and baked at a temperature of 780°C in an N2 atmosphere to form external electrodes, thereby producing a multilayer ceramic capacitor. This was carried out for all the Ni pastes described above, to obtain the samples in Table 1 or Table 2. In Table 1 or Table 2, the samples marked with an * next to the sample number are comparative examples that do not satisfy the requirements of the present invention. The external dimensions of the obtained multilayer ceramic capacitor were width (W): 1.6 mm, length (L): 3.2 mm, and thickness (T): 0.7 mm. The thickness of the internal electrode layer was 1.2 μm, and the thickness of the ceramic dielectric layer interposed between the internal electrodes was 4.0 μm. The area of ​​the opposing electrode per dielectric layer was 3.25 mm. 2 It was.

[0070] <Evaluation of characteristics> For each multilayer ceramic capacitor (samples in Tables 1 and 2) prepared as described above, a high-temperature load test was performed using the method described below. The continuity of the internal electrode layer was evaluated, and the vicinity of the interface between the ceramic dielectric layer and the internal electrode layer was observed. It was confirmed that a diffusion region (diffusion layer) was formed in which the concentration of Ta or Nb increases in the direction from the internal electrode layer side to the ceramic dielectric layer side, reaches a concentration peak, and then decreases. (1) High temperature load test Fifteen pieces were sampled from each sample, and a high temperature load test was performed under conditions of 180℃ and 60V. The time required for the insulation resistance to drop by one digit was determined as the failure time of each multilayer ceramic capacitor. This failure time was then plotted against a Weibull curve to determine the MTTF (mean time to failure). The evaluation results of MTTF are shown in Table 1 or Table 2, and are also summarized in Figure 1 and Figure 2, respectively. (2) Continuity evaluation of internal electrode layers Each sample of the multilayer ceramic capacitor was cut at a plane perpendicular to the internal electrode layer and observed with a SEM (scanning electron microscope). The observation magnification was 1000 times, and 10 internal electrodes were randomly selected from the observation field, and the ratio of the part where the electrode was present to the total length was measured and evaluated as continuity. Here, continuity of 90% or more was marked with ◎, 80-90% was marked with ○, and less than 80% was marked with ×, and these are all shown in Table 1 or Table 2.

[0071] [Table 1] 1) Mass parts per 100 mass parts of spherical nickel powder 2) Ratio of MTFF of each sample to MTFF of sample 1A (without Ta2O5 added) (MTFF of each sample / MTTF of sample 1A)

[0072] [Table 2] 1) Mass parts per 100 mass parts of spherical nickel powder 2) Ratio of MTFF of each sample to MTFF of sample 1A (without Nb2O5 added) (MTFF of each sample / MTTF of sample 1A)

[0073] As shown in Table 1 and Table 2, for the sample without Ta2O5 or Nb2O5 mixed (sample number 1A), the MTTF increased in all samples (sample numbers 2A to 10A and 12A to 20A) with Ta2O5 or Nb2O5 mixed within the range defined in the present invention. Also, the continuity of the internal electrodes showed 90% or more in sample numbers 2A to 7A and 12A to 16A, and showed 80 to 90% in sample numbers 8A to 10A and 17A to 20A. On the other hand, in the samples (sample numbers 11A and 21A) where the mixing of Ta2O5 or Nb2O5 exceeded the range defined in the present invention, the MTTF became lower than that of the sample without Ta2O5 or Nb2O5 mixed (sample number 1A), and the continuity of the internal electrodes was less than 80%. From the above, in order to improve the high-temperature load life, it is preferable to mix 0.025 to 2.50 parts by mass of Ta2O5 or 0.01 to 1.80 parts by mass of Nb2O5 per 100 parts by mass of spherical nickel powder. Furthermore, if it is within the range of 0.025 to 0.80 parts by mass of Ta2O5 or 0.01 to 0.50 parts by mass of Nb2O5, it is possible to further improve the high-load life without impairing the continuity of the internal electrodes.

[0074] <<(D3) Stabilized Zirconia (SZ)>> (Examples 2 and Comparative Example 1) <Manufacture of Ni Paste and Multilayer Ceramic Capacitor> (Preparation of Ni Paste) As Comparative Example 1, for 100.0 g of spherical nickel powder with an average particle size of 0.3 μm, ZrO2 was prepared at a ratio of the number of moles shown in Table 3. Further, as a co-material powder, 10.0 g of BaTiO3 powder with an average particle size of 0.05 μm, 6.0 g of ethyl cellulose (binder resin), 2.0 g of surfactant, 1.0 g of plasticizer, and 100.0 g of dihydroterpineol acetate (organic solvent) were mixed at a ratio, and Ni paste was prepared by kneading using a three-roll mill. In addition, as Example 2, a Ni paste was prepared in the same manner as in Comparative Example 1, except that 3.0 mol % yttria stabilized zirconia (3.0-YSZ) was used in place of ZrO2 in a ratio corresponding to the number of moles shown in Table 4.

[0075] (Manufacturing of multilayer ceramic capacitors) Next, a polyvinyl butyral binder, ethanol, and an additive to adjust the capacitor characteristics were added to BaTiO3 powder with an average particle size of 0.2 μm, which is the main component of the ceramic green sheets, and wet-mixed in a media mill to prepare a ceramic slurry. This ceramic slurry was formed into a sheet by a die coater method to prepare a ceramic green sheet having a thickness of 5.5 μm. Next, the Ni pastes of Example 2 and Comparative Example 1 were printed on the ceramic green sheets in rectangular patterns of 1.5 mm x 3.0 mm, and then dried to form an internal electrode dry film. The thickness of the internal electrode dry film was 1.5 μm. The ceramic green sheets having the internal electrode dry film were stacked so that the number of dielectric effective layers was 50, and the ceramic green sheets were heated at 90° C. and subjected to a pressure of 1250 kg / cm. 2 The mixture was pressed and molded under a pressure of 1000 MPa to obtain an unfired ceramic laminate. This ceramic laminate was heated to 700°C in an atmosphere of N2-0.1%H2-H2O gas to burn the binder, and then the oxygen partial pressure at 1220°C was 1×10 -8 The material was heated at a rate of 5°C / min in a reducing atmosphere of N2-0.1% H2-H2O gas at 1 atm, and then held at 1220°C for 2 hours to sinter and densify it. After that, in the cooling stage, a reoxidation treatment was performed at 1000°C for 3 hours in an N2-H2O gas atmosphere to obtain a laminated ceramic body. Next, a Cu paste for forming external electrodes containing Cu powder and BaO-based glass frit was applied to both end faces of the multilayer ceramic body, and baked at a temperature of 780°C in an N2 atmosphere to form external electrodes, thereby producing a multilayer ceramic capacitor. This was performed for all the Ni pastes described above, thereby obtaining Samples 1B to 21B in Table 3 or Table 4. In Table 3 or Table 4, the samples marked with an * next to the sample number are comparative examples that do not satisfy the requirements of the present invention. The external dimensions of the obtained multilayer ceramic capacitor were width (W): 1.6 mm, length (L): 3.2 mm, and thickness (T): 0.7 mm. The thickness of the internal electrode layer was 1.2 μm, and the thickness of the ceramic dielectric layer interposed between the internal electrodes was 4.0 μm. The area of ​​the opposing electrode per dielectric layer was 3.25 mm. 2 It was.

[0076] <Evaluation of characteristics> For each multilayer ceramic capacitor (samples in Table 3 or Table 4) prepared as described above, a high-temperature load test was performed by the method described below, and the continuity of the internal electrode layer was evaluated, and the vicinity of the interface between the ceramic dielectric layer and the internal electrode layer was observed. It was confirmed that the concentration of Zr and / or Y, which is a metal element in the stabilizer, increases in the direction from the internal electrode layer side to the ceramic dielectric layer side, reaches a concentration peak, and then decreases, forming a diffusion region (diffusion layer).

[0077] (1) High temperature load test Fifteen pieces were sampled from each sample, and a high temperature load test was performed under the conditions of 180°C and 60V. The time required for the insulation resistance to drop by one digit was determined as the failure time of each multilayer ceramic capacitor. This failure time was then plotted against a Weibull curve to determine the MTTF (mean time to failure). The evaluation results of MTTF are shown in Table 3 or Table 4. In order to compare Comparative Example 1 and Example 2, the respective MTTFs are summarized in FIG. Furthermore, the MTTF of the stabilized zirconia (3.0-YSZ) added relative to the MTTF of the zirconia (ZrO2) added in Comparative Example 1 was determined, and the results are summarized in Table 5 and FIG.

[0078] (2) Continuity evaluation of internal electrode layers Each sample of the multilayer ceramic capacitor was cut at a plane perpendicular to the internal electrode layer and observed with a SEM (scanning electron microscope). The observation magnification was 1000 times, and 10 internal electrodes were randomly selected from the observation field, and the ratio of the part where the electrode was present to the total length was measured and evaluated as continuity. Here, continuity of 90% or more was marked with ◎, 80-90% was marked with ○, and less than 80% was marked with ×, and these are shown in Table 3 or Table 4.

[0079] [Table 3] 1) Number of moles per 100g of spherical nickel powder 2) Ratio of the MTTF of each sample to the MTTF of sample 1B (no additives) (MTTF of each sample / MTTF of sample 1B)

[0080] [Table 4] 1) Number of moles per 100g of spherical nickel powder 2) Ratio of the MTTF of each sample to the MTTF of sample 1B (no additives) (MTTF of each sample / MTTF of sample 1B)

[0081] [Table 5] 1) The ratio of the MTTF of the 3.0-YSZ-added sample to the MTTF of the sample with the same mole of ZrO2 added (MTTF of the 3.0-YSZ-added sample / MTTF of the sample with the same mole of ZrO2 added)

[0082] As shown in Tables 3 to 5 and Figures 3 to 4, the MTTF was increased in all samples (samples 12B to 20B) in which stabilized zirconia (3.0-YSZ) was mixed within the range specified in the present invention, compared to the sample (sample 1B) in which no ZrO2 or stabilized zirconia (3.0-YSZ) was mixed. In addition, the MTTF was higher in all samples (samples 12B to 20B) in which stabilized zirconia (3.0-YSZ) was mixed within the range specified in the present invention, compared to the samples (samples 2B to 10B) in which the same moles of zirconia (ZrO2) were added. In addition, the continuity of the internal electrodes was 90% or more for Samples 12B to 18B and 80 - 90% for Samples 19B to 20B. On the other hand, in the sample (Sample 21B) where the mixing of stabilized zirconia (3.0 - YSZ) exceeded the range defined in the present invention, the MTTF was lower and the continuity of the internal electrodes was less than 80% compared to the sample (Sample 11B) mixed with zirconia (ZrO2). From the above, by mixing 0.05×10 -2 to 2.20×10 -2 moles of stabilized zirconia (3.0 - YSZ) per 100 g of spherical nickel powder, the high - temperature load life can be improved compared to the cases of no addition and addition of zirconia (ZrO2). Furthermore, within the range of 0.05×10 -2 to 1.40×10 -2 moles, it is possible to further improve the high - load life without impairing the continuity of the internal electrodes.

[0083] (Example 3) (Manufacture of Ni paste and multilayer ceramic capacitor) (Preparation of Ni paste) For 100.0 g of spherical nickel powder with an average particle size of 0.3 μm, stabilized zirconia (X - YSZ) powder stabilized with yttria (Y2O3) in the content (X mol%) shown in Table 6 was prepared at a ratio of 0.80×10 -2 moles. Furthermore, as a co - material powder, 10.0 g of BaTiO3 powder with an average particle size of 0.05 μm, 6.0 g of ethyl cellulose (binder resin), 2.0 g of surfactant, 1.0 g of plasticizer, and 100.0 g of dihydroterpineol acetate (organic solvent) were mixed, and Ni paste was prepared by kneading using a three - roll mill.

[0084] (Manufacture of multilayer ceramic capacitor) Except for using the above Ni paste, the same procedure as in Example 2 was followed. By performing this for all of the above - mentioned Ni pastes, Samples 22B to 28B in Table 6 were obtained.

[0085] <Characteristics evaluation> Except for using the sample obtained above, the same procedure as in Example 2 was carried out. The results are shown in Table 6.

[0086] The ratio of the MTTF (samples 16B, 22B to 28B) when the stabilizer content was changed without changing the stabilizer content (X-YSZ) content, to the MTTF (sample 1B) when neither zirconia (ZrO2) nor stabilized zirconia (YSZ) was added, i.e., MTTF (X-YSZ) / MTTF (no additive), is shown by the black circle in FIG. 5 (vertical axis on the left). In addition, the ratio of the MTTF of similarly stabilized zirconia (X-YSZ) (samples 16B, 22B to 28B) to the MTTF of the same amount of zirconia (ZrO2) added (sample 6B), i.e., MTTF (X-YSZ) / MTTF (ZrO2), is shown in the squares in Figure 5 (vertical axis on the right).

[0087] [Table 6] 1) X refers to the mole percentage of Y2O3 contained in stabilized zirconia (YSZ). 2) Ratio of the MTTF of each sample to the MTTF of sample 1B (no additives) (MTTF of each sample / MTTF of sample 1B) 3) Ratio of MTTF of each sample to sample 6B with the same mole of ZrO2 added (MTTF of each sample / MTTF of sample 6B)

[0088] As shown in Table 6 and FIG. 5, no correlation was found between the content of the stabilizer (Y2O3) in the stabilized zirconia (YSZ) and the continuity of the electrode film. However, when the content of the stabilizer (Y2O3) is 50.0 mol% or more, the MTTF is lower than that of the comparative example (sample 6B) with added zirconia (ZrO2) and the comparative example (sample 1B) without added zirconia. Therefore, in the stabilized zirconia (YSZ) of the present invention, good results can be obtained if the content of the stabilizer (Y2O3) is in the range of more than 0.0 mol% and not more than 45.0 mol%, preferably more than 0.0 mol% and not more than 40.0 mol%, and particularly preferably in the range of 8.0 to 25.0 mol%.

[0089] (Example 4) (Manufacture of Ni paste and multilayer ceramic capacitor) (Preparation of Ni paste) To 100.0 g of spherical nickel powder with an average particle size of 0.3 μm, 0.80×10 -2 mol of stabilized zirconia (10.0-SZ) powder containing 10.0 mol% of the stabilizer of the type shown in Table 7 was prepared. Further, as a co-material powder, 10.0 g of BaTiO3 powder with an average particle size of 0.05 μm, 6.0 g of ethyl cellulose (binder resin), 2.0 g of surfactant, 1.0 g of plasticizer, and 100.0 g of dihydroterpineol acetate (organic solvent) were mixed in a ratio, and kneaded using a three-roll mill to prepare a Ni paste.

[0090] (Manufacture of multilayer ceramic capacitor) Except for using the above Ni paste, the same procedure as in Example 2 was followed. By performing this on all of the above Ni paste, Samples 29B to 31B in Table 7 were obtained.

[0091] (Characteristic evaluation) Except for using the samples obtained above, the same procedure as in Example 2 was followed. The results are also shown in Table 7.

[0092] [Table 7] 1) Ratio of MTTF of each sample to MTTF of Sample 1B (MTTF of each sample / MTTF of Sample 1B) 2) Ratio of MTTF of each sample to MTTF of Sample 6B with the same molar amount of ZrO2 added (MTTF of each sample / MTTF of Sample 6B)

[0093] From the results in Table 7, it was found that even when using calcia (CaO), magnesia (MgO), and scandia (Sc2O3) as stabilizers, similar to yttria (Y2O3), the high-temperature load life can be improved without reducing the continuity of the internal electrode film.

[0094] <<Additive containing Al (D4)>> (Example 5) <Manufacture of Ni paste and multilayer ceramic capacitor> For 100.0 g of spherical nickel powder with an average particle size of 0.3 μm, Al2O3 was added at the ratio shown in parts by mass in Table 8. As co-material powder, 10.0 g of BaTiO3 powder with an average particle size of 0.05 μm, 6.0 g of ethyl cellulose (binder resin), 2.0 g of surfactant, 1.0 g of plasticizer, and 100.0 g of dihydroterpineol acetate (organic solvent) were mixed at the ratio shown, and kneaded using a three-roll mill to prepare Ni paste. Next, a polyvinyl butyral-based binder, ethanol, and an additive for adjusting capacitor characteristics were added to BaTiO3 powder with an average particle size of 0.2 μm, which is the main component of the ceramic green sheet, and wet-mixed using a media mill to prepare a ceramic slurry. This ceramic slurry was sheet-formed by the die coater method to prepare a ceramic green sheet with a thickness of 5.5 μm. Subsequently, Ni paste was printed on this ceramic green sheet in a rectangular pattern of 1.5 mm × 3.0 mm, and then dried to form an internal electrode dry film. The thickness of the internal electrode dry film was 1.5 μm. The ceramic green sheet having the internal electrode dry film was stacked so that the dielectric effective layer had 50 layers, and pressure of 1250 kg / cm was applied at 90 °C 2 for crimping and cutting to obtain an unfired ceramic laminate. This ceramic laminate was heated to 700 °C in an atmosphere composed of N2 - 0.1% H2 - H2O gas to burn the binder, and then in a reducing atmosphere composed of N2 - 0.1% H2 - H2O gas with an oxygen partial pressure of 1 × 10 -8 atm at a heating rate of 5 °C / min, held at 1220 °C for 2 hours for sintering densification, and then, in the cooling stage, re-oxidation treatment was performed at 1000 °C for 3 hours in an N2 - H2O gas atmosphere to obtain a multilayer ceramic body. Next, a Cu paste for forming external electrodes containing Cu powder and BaO-based glass frit was applied to both end faces of the multilayer ceramic body, and baked at a temperature of 780°C in an N2 atmosphere to form external electrodes, thereby producing a multilayer ceramic capacitor. This was carried out for all the Ni pastes described above to obtain the samples in Table 8. In Table 8, samples marked with an * next to the sample number are comparative examples that do not satisfy the requirements of the present invention. The external dimensions of the obtained multilayer ceramic capacitor were width (W): 1.6 mm, length (L): 3.2 mm, and thickness (T): 0.7 mm. The thickness of the internal electrode layer was 1.2 μm, and the thickness of the ceramic dielectric layer interposed between the internal electrodes was 4.0 μm. The area of ​​the opposing electrode per dielectric layer was 3.25 mm. 2 It was.

[0095] <Evaluation of characteristics> For each multilayer ceramic capacitor (samples in Table 8) prepared as described above, a high-temperature load test was performed using the method described below. The continuity of the internal electrode layer was evaluated, and the vicinity of the interface between the dielectric layer and the internal electrode layer was observed. It was confirmed that the Al concentration increases in the direction from the internal electrode layer side to the ceramic dielectric layer side, reaches a concentration peak, and then a diffusion region (diffusion layer) where the concentration decreases was formed. (1) High temperature load test Fifteen pieces were sampled from each sample and subjected to a high temperature load test at 180℃ and 60V. The time required for the insulation resistance to drop by one digit was determined as the failure time of each multilayer ceramic capacitor. This failure time was then plotted against a Weibull curve to determine the MTTF (mean time to failure). The MTTF evaluation results are shown in Table 8 and summarized in Figure 6. (2) Continuity evaluation of internal electrode layers Each sample of multilayer ceramic capacitor was cut at a plane perpendicular to the internal electrode layer and observed with a SEM (scanning electron microscope). The observation magnification was 1000 times, and 10 internal electrodes were randomly selected from the observation field, and the ratio of the part where the electrode was present to the total length was measured and evaluated as continuity. Here, continuity of 90% or more was marked as ◎, 80-90% was marked as ○, and less than 80% was marked as ×, and these are all shown in Table 8.

[0096] [Table 8] 1) Mass parts per 100 mass parts of spherical nickel powder 2) Ratio of MTFF of each sample to MTFF of sample 1C (no Al2O3 added) (MTFF of each sample / MTTF of sample 1C)

[0097] As shown in Table 8, the MTTF increased in all samples (sample numbers 2C to 15C) in which Al2O3 was mixed within the range specified in the present invention, compared to the sample (sample number 1C) in which Al2O2 was not mixed. Moreover, the continuity of the internal electrodes was 90% or more in sample numbers 2C to 11C, and 80 to 90% in sample numbers 12C to 15C. On the other hand, in the sample (sample number 16C) in which the amount of Al2O3 mixed exceeded the range specified in the present invention, the MTTF was lower than that of the sample (sample number 1C) in which Al2O3 was not mixed, and the continuity of the internal electrodes was less than 80%. From the above, in order to improve the high-temperature load life, it is preferable to mix 0.10 to 5.50 parts by mass of Al2O3 per 100 parts by mass of spherical nickel powder, and if the amount is within the range of 0.10 to 2.30 parts by mass, it is possible to further improve the high-temperature load life without impairing the continuity of the internal electrode.

Claims

1. A method for forming a diffusion region of at least one element selected from the group consisting of Ta, Nb, Zr and metal elements in a stabilizer at and near interfaces between adjacent internal electrode layers and the ceramic dielectric layers in a multilayer ceramic capacitor having a ceramic laminate in which a plurality of ceramic dielectric layers and a plurality of internal electrode layers containing Ni are alternately laminated, and an external electrode formed on an outer surface of the ceramic laminate, the method comprising the steps of: At least, the method includes a step of stacking a predetermined number of ceramic green sheets forming the ceramic dielectric layers and internal electrode paste films forming the internal electrode layers alternately to prepare a laminate, and firing the laminate at 900 to 1400° C. in a reducing atmosphere; The internal electrode paste film is formed using a Ni paste containing (A) a conductive powder mainly containing Ni, (B) a binder resin, (C) an organic solvent, and (D) an additive, And the (D) additive is (D1) Ta per 100.0 parts by mass of the (A) Ni-based conductive powder 2 O 5 An additive containing Ta in a range of 0.025 to 0.80 parts by mass in terms of Ta conversion; (D2) Nb per 100.0 parts by mass of the (A) Ni-based conductive powder 2 O 5 An additive containing Nb in a range of 0.010 to 0.50 parts by mass in terms of Nb content; and (D3) 0.05×10 per 100 g of the (A) Ni-based conductive powder -2 ~1.40 x 10 -2 Stabilized zirconia (SZ) in which the crystal structure of zirconia is stabilized by a stabilizer contained in an amount within the range of 8.0 to 25.0 mol %. At least one selected from the group consisting of A method for forming a diffusion region in a multilayer ceramic capacitor, comprising:

2. the interface and its vicinity are a region from the interface between the adjacent internal electrode layer and the ceramic dielectric layer to a ceramic dielectric layer side of 1 / 16 of the thickness of the ceramic dielectric layer, and a region from the interface to the internal electrode layer side of 1 / 2 of the thickness of the internal electrode layer, In the diffusion region, the concentration of at least one element selected from the group consisting of Ta, Nb, Zr and a metal element in a stabilizer has a concentration distribution that increases in a direction from the internal electrode layer side to the ceramic dielectric layer side, reaches a concentration peak, and then decreases.

2. The method for forming a diffusion region in a multilayer ceramic capacitor according to claim 1,

3. 3. The method for forming a diffusion region in a multilayer ceramic capacitor according to claim 1, wherein the metal element in the stabilizer is at least one selected from the group consisting of Y, Ca, Mg and Sc.

4. a ceramic laminate in which a plurality of ceramic dielectric layers and a plurality of internal electrode layers containing Ni are alternately laminated; an external electrode formed on an outer surface of the ceramic laminate; Equipped with A diffusion region of at least one element selected from the group consisting of Ta, Nb, Zr and metal elements in a stabilizer is provided at and near the interface between the adjacent internal electrode layer and the ceramic dielectric layer, the interface and its vicinity are a region from the interface between the adjacent internal electrode layer and the ceramic dielectric layer to a ceramic dielectric layer side of 1 / 16 of the thickness of the ceramic dielectric layer, and a region from the interface to the internal electrode layer side of 1 / 2 of the thickness of the internal electrode layer, a multilayer ceramic capacitor, characterized in that in the diffusion region, the concentration of at least one element selected from the group consisting of Ta, Nb, Zr and metal elements in a stabilizer has a concentration distribution in which the concentration increases in a direction from the internal electrode layer side to the ceramic dielectric layer side, reaches a concentration peak, and then decreases.

5. 5. The multilayer ceramic capacitor according to claim 4, wherein the metal element in the stabilizer is at least one selected from the group consisting of Y, Ca, Mg and Sc.

6. (A) a conductive powder mainly containing Ni; (B) a binder resin; and (C) an organic solvent; (D) an additive; and Contains And, the (D) additive is, (D1) Ta per 100.0 parts by mass of the (A) Ni-based conductive powder. 2 O 5 An additive containing Ta in a range of 0.025 to 0.80 parts by mass in terms of Ta conversion; (D2) Nb per 100.0 parts by mass of the (A) Ni-based conductive powder 2 O 5 An additive containing Nb in a range of 0.010 to 0.50 parts by mass in terms of Nb content; and (D3) The crystal structure of zirconia is stabilized by a stabilizer in the range of 8.0 to 25.0 mol %, and the (A) Ni-based conductive powder has a content of 0.05 × 10 -2 ~1.40 x 10 -2 Stabilized zirconia (SZ) in the molar range At least one selected from the group consisting of The Ni paste is characterized by:

7. In the case where the (D3) stabilized zirconia (SZ) is contained, the stabilizer is Y 2 O 3 , CaO, MgO and Sc 2 O 3 The Ni paste according to claim 6, characterized in that it is one or more selected from the following.

Citation Information

Patent Citations

  • Multilayer ceramic capacitor

    JP1996241828A

  • Ni powder, and ni paste using the same

    JP1999021644A

  • Electrode composition of capacitor and electrode paste using it

    JP2000049031A

  • Powder material, its production, thick film electrically conductive paste using the power material and laminated ceramic capacitor using the paste

    JP2000063901A

  • Conductive paste, and laminated ceramic capacitor and method for manufacturing it

    JP2001101926A